A Smart T(1)-weighted MRI Contrast Agent for Uranyl Cation based on a DNAzyme-Gadolinium Conjugate - Xu, Weichen (2013)
Rational design of smart MRI contrast agents with high specificity for metal ions remains to be a challenge. Here, we report a general strategy for the design of smart MRI contrast agents for detecting metal ions based on conjugation of a DNAzyme with a gadolinium complex. The 39E DNAzyme, which has high selectivity for UO(2)(2+), was conjugated to Gd(III)-DOTA and streptavidin. The binding of UO(2)(2+) to its 39E DNAzyme resulted in the dissociation of Gd(III)-DOTA from the massive streptavidin, leading to a decrease in T(1) correlation time, and a change in MRI signal.